Analisa Temperatur Pemotongan Pada Pembubutan AISI 304 Menggunakan Cairan Pendingin Virgin Coconut Oil (VCO) Dengan Metode Minimum Quantity Lubrication (MQL) - Aksamanika Putra, Made; Tirta Nindhia, Tjokorda Gde; Dwijana, I Gusti Komang (Teknik Desain Mekanika; Vol 12 No 4 (2023): Oktober 2023 : Teknik Desain Mekanika, 2023)
Abstractt In metal processing coolant fluids derived from petroleum are commonly used. However, the use of petroleumbased coolant fluids has detrimental effects on the environment, such as soil and water pollution, as well as potential health problems like skin irritation, respiratory disorders, and even cancer. Therefore, several methods have been developed to reduce the use of petroleum-based coolant fluids and minimize the resulting waste. One alternative coolant fluid that can be used is vegetable oil. The objective of this research is to evaluate the use of vegetable oil, particularly Virgin Coconut Oil (VCO), with the Minimum Quantity Lubrication (MQL) method as a coolant fluid in the turning process of AISI 304 metal. The turning process is performed using carbide insert cutting tools of the DCMT070204 type. This study involves three variations of cutting depths, namely 0.30mm, 0.60mm, and 0.90mm. Specimens with a diameter of 1 inch and a length of 150mm are used, and the turning process is conducted along a 100mm length with three repetitions for each cutting depth variation. The research results indicate that the use of Virgin Coconut Oil (VCO) as a coolant fluid with the Minimum Quantity Lubrication (MQL) method effectively cools down the cutting tools and prevents overheating. The average turning temperature using this coolant fluid was found to be 5.5% lower. Keywords: Turning process, coolant, MQL system.